1972
DOI: 10.1055/s-0028-1097084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypercalcemia, Hypercalcemia and Calcitonin on Glucose Stimulated Insulin Secretion in Man

Abstract: In an additional experiment PTH and DBcAMP effects on serum 47 Ca activity were measured in PTX rats with prelabelled bone: DBcAMP did not cause a significant rise in serum 47 Ca as did PTH. ConcIusionsDBcAMP elevates serum Ca by increased intestinal Ca absorption. The amount of Ca being additionally absorbed after DBcAMP treatment was not utilized by deposition in bone, but excreted in the urine. DBcAMP did not alter serum Ca in starving rats. This and the absence of increased 47Ca remobilization from prelabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Numerous factors may contribute to this alteration and the mechanism remains speculative. The increased CT level might represent a secondary response to insulin hypersecretion and to the increase in intracellular Ca concentration: C T is known to inhibit glucose-stimulated insulin secretion (24) and to stimulate Ca efflux from the cells of various tissues (25). The increase in C T levels might also be secondary to the delayed rise in the glucagon levels which occurs after glucose and insulin increase: in fact glucagon is known to release CT (26).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors may contribute to this alteration and the mechanism remains speculative. The increased CT level might represent a secondary response to insulin hypersecretion and to the increase in intracellular Ca concentration: C T is known to inhibit glucose-stimulated insulin secretion (24) and to stimulate Ca efflux from the cells of various tissues (25). The increase in C T levels might also be secondary to the delayed rise in the glucagon levels which occurs after glucose and insulin increase: in fact glucagon is known to release CT (26).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous glucose tolerance was assessed in twelve patients by giving glucose 0.33 gikg body weight i.v. (Ziegler et al, 1972). Plasma for insulin assay was separated by centrifugation and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…High or low calcium levels were found to enhance, or suppress, glucose-induced insulin secretion respectively. Acute experiments in man, in w h c h hypercalcaemia was induced by calcium infusion, also revealed increased glucoseinduced insulin output (Ziegler et al, 1972). Few studies in man, however, have focused attention on the effects on insulin secretion of sustained variations in plasma calcium concentration within a pathophysiological range (Kim et al, 1971 ;Yasuda et al, 1975) and this was, therefore, the purpose of this study.…”
mentioning
confidence: 95%
“…Contrary to Gig, reports on the effect of Ct on glucose metabolism in man are scarce. In man, Ziegler et al (1972) described a decline of IRI and a decrease of rate of glucose assimilation, Blahos, Svoboda and Hoschl (1976) observed a rise of BS without any changes of IRI after administration, and more recently, Cantalamessa et al (1978) have found a decrease of IRI (both native and stimulated) and a blunted response of GH to arginine stimulation.…”
Section: Discussionmentioning
confidence: 96%